If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + y + -6y = 11 Combine like terms: y + -6y = -5y 11 + -5y = 11 Add '-11' to each side of the equation. 11 + -11 + -5y = 11 + -11 Combine like terms: 11 + -11 = 0 0 + -5y = 11 + -11 -5y = 11 + -11 Combine like terms: 11 + -11 = 0 -5y = 0 Solving -5y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-5'. y = 0 Simplifying y = 0
| 4x(-6.3)=8.7findthex | | 32+32+x=90 | | 32+32+x=180 | | 4x(-6.3)=8.7 | | 1x+(-3)=-4 | | 7n+30=y | | -3(4x-6)=6 | | 7c^2-175=0 | | 7c-175=0 | | Y=x(x)-x-6 | | 13-w=3-w | | 8-8y=-4(4+8) | | 1024^(-1/5) | | y=8+9x | | 8-8y=-4 | | x+7+.33*x=1.5*x-2 | | 7m^2+km+5=0 | | ln(x^2+15)=ln(x)+ln(8) | | x+7+.33*x=1.33*x-2 | | 21=7e^2x | | 27x-90x^2=0 | | 9(5k+2)+4(7-10k)= | | y+4=-5(x-8) | | -6a-b+11c-8-7a=10b-3x-9 | | -4/6=n/3 | | -2x=7+y | | 18-2x=4x-6 | | 3w=15-2w | | 1/3x-2x=28 | | x*3/8x=6 | | (1/2)-(1/(2(1-2x)^2)) | | 11u=8u+15 |